Quantitative proteomics and single-nucleus transcriptomics of the sinus node elucidates the foundation of cardiac pacemaking - Nora Linscheid (Nature Portfolio, 2019)
The sinus node generates rhythmic heartbeat but the molecular basis of pacemaking is still under debate. Here, the authors combine quantitative proteomics and single-nucleus transcriptomics to characterize the molecular composition of the sinus node and provide insights into the underpinnings of pacemaking.